3D Alk‐MXene@Fe3O4 as Cathode Additive for Rechargeable Lithium−Sulfur Batteries. Issue 3 (18th November 2021) - Zhang, Zekun; Wang, Bo; Han, Ruimei; Jin, Fan; Zhang, Nan; Zhang, Tianren; Wang, Dianlong
Abstract : Lithium−sulfur battery (LSB) is one of the most promising next‐generation batteries due to its high energy density and low cost. However, the serious shuttle effect, large volume change, and poor conductivity have hindered their commercialization. Herein, alk‐MXene@Fe3 O4 composite is synthesized through ultrasonic treatment of alkalized MXene and Fe3 O4 and it is used as additive in the sulfur cathode. The results indicate that Alk‐MXene@Fe3 O4 additive can anchor polysulfides by the strong polar adsorption and accelerate the conversion of the LiPSs. The cathode with Alk‐MXene@Fe3 O4 retains a substantially stable discharge capacity of 681.7 mAh g −1 after 120 cycles at a rate of 0.2 C, which is equivalent to 58.6% of the initial discharge capacity (1163 mAh g −1 ), and the corresponding capacity decay per cycle is 0.35%. At a rate of 1 C, it can still retain 595 mAh g −1 after 200 cycles. It has important reference value for the development of cathode additives to improve the performance of active sulfur. Abstract : A 3D Alk‐MXene@Fe3 O4 composite through ultrasonic treatment of alkalized MXene and Fe3 O4 is prepared and used as lithium−sulfur battery cathode additive, which can anchor polysulfides by the strong polar adsorption and accelerate the conversion of the LiPSs and thus effectively inhibits the "shuttle effect" of polysulfides during the cycling process.